Olive oil, diet and colorectal cancer: an ecological study and a hypothesis. - Stoneham, M; Goldacre, M; Seagroatt, V; Gill, L (2000)
STUDY OBJECTIVES: Colorectal cancer (CRC) is a common cancer in many western countries and is probably caused in part by dietary factors. Southern European countries have lower incidence rates of CRC than many other western countries. It was postulated that, because olive oil is thought to influence bile salt secretion patterns in rats, it may influence the occurrence of CRC. The purpose of this study was to compare national levels of dietary factors, with particular reference to olive oil, with national differences in CRC incidence. DESIGN: Ecological study using existing international databases. Incidence rates for CRC, food supply data, and olive oil consumption data were extracted from published sources, combined, and analysed to calculate the correlations between CRC and 10 dietary factors. Associations were then explored using stepwise multiple regression. SETTING: 28 countries from four continents. MAIN RESULTS: 76% of the intercountry variation in CRC incidence rates was explained by three significant dietary factors-meat, fish and olive oil-in combination. Meat and fish were positively associated, and olive oil was negatively associated, with CRC incidence. CONCLUSION: Olive oil may have a protective effect on the development of CRC. The proposed hypothesis is that olive oil may influence secondary bile acid patterns in the colon that, in turn, might influence polyamine metabolism in colonic enterocytes in ways that reduce progression from normal mucosa to adenoma and carcinoma.